DESIGN OF ECO GREEN WIND TURBIN USING FUZZY LOGIC ON SAHARA DESERT - Ahsraf Ashraf Khalil; Muhamad Haddin; Arief Marwanto; Muhammad Qomaruddin (Universitas Islam Sultan Agung, 2022)
In development of wind turbine, the government of Libya has assignment Libya electric co. To develop wind turbine in Sahara Desert beginning of 2001. The officer the took a surveying of wind speed and the environment of the Sahara Desert. The surveying has shown that wind speed of Sahara Desert is class 4 and 5. Therefore is suitable to develop wind turbine to produce electrical power for RL (Resistor Load). Based on the argument above, so this research entitled: “Analysis Of Eco Green Wind Turbine Design For Sahara Desert Using Fuzzy Logic”. The objectives of this research are: to design and development of eco green vertical axis wind turbines (VAWT) in Sahara Desert, to analysis of suitable eco green vertical axis wind turbines (VAWT) in Sahara Desert using MATLAB and to analysis of how fuzzy logic use in wind turbine design. Research model used input process in Matlab simulation and output is the design and analysis of efficiency wind turbines.